From Broadcast to On-Demand: Innovations Shaping the Video Streaming Landscape—Case Study: RaiPlay - Alexandra Ioanid; Denisa Iliescu (IEEE Access, 2025)
This study explores the rapid growth of the video streaming industry, following its journey from early technological challenges to its current prominence in global entertainment. Using an extensive literature review paired with a real-life example on the digitalization of RaiPlay, the research explores how technological innovations including high-speed internet, big data or AI-driven platforms have transformed users’ streaming experience and influence viewer’s behavior. The study highlights how subscription-based and advertising-based commercial models have progressively inclined viewers on modern entertainment, while new developments in video quality and innovations in adaptive streaming have improved the user experience. However, this research is limited by the rapidly evolving technological landscape. Looking forward, emerging trends in technology are going to keep transforming this challenging industry, offering new directions for exploration.